Challenges for the promotion of Integral Education: experiences developed by cities in Rio de Janeiro (Research, Society and Development, 2020)
This study reflects on full-time schools in the state of Rio de Janeiro. The social and historical conditions that determine it are addressed, in addition to the challenges that the school, management team and faculty face in the face of contemporary demand. A qualitative research was carried out, and as support, interviews were carried out using forms provided by the Google Forms platform. 4 managers from 3 schools located in the state of Rio de Janeiro and 9 teachers from the same schools participated. The objective of this study was to understand what are the main challenges of schools that had to adhere to the full-time journey and how these professionals are placed regarding their work in the education network in which they work, since they are responsible for the organization of the school routine and determination of teaching work. It was found that, among the various difficulties faced by full-time institutions, the main ones are: precarious teaching, school linked to social protection and lack of physical structure. It is known that public education in Brazil is taking slow steps towards the desired future, however it is reinforced that academic research and the involvement of society are of paramount importance to achieve improvements within school public policies.